سلسلہ قادریہ محمودیہ کے اسباق کی متابعت اصطلاحات ِتصوف کی روشنی میں تجزیاتی مطالعہ: Teaching of Qadriyya Mahmoodiyah series of following in the light of Sufism terms An Analytical Study - علامہ اکرم ولی; ڈاکٹر رشاد احمد (Al Basirah, 2021)
Islamic mysticism is one of the famous and important Corrective Movement, which has different ṭuruq or "orders. Order of Qadriyya Mahmoodiyah is one of these Turuq which has some specific Adhkar / Sufi ritual for recitation like other Turuq.In this article the sequence of the these Adhkar is discussed in the light of Islamic mysticism. This study will help the scholars to understand the Order of Qadriyya Mahmoodiyah and elaborate the importance of this Sufi ritual and also the sequence among the Adhkar.